A criptoteologia messiânica de Clarice Lispector frente à crise do século XXI. Análise da crônica “Mineirinho” - Sawala, Wojciech (Studia Romanica Posnaniensia, 2019)
The article is aimed at pointing out the messianic dimension of Clarice Lispector’s writings. We intend to describe the post-secular vision of the collective redemption embedded in her work as essentially opposed to the vulgarized notion of political messianism. Its core element is the establishment of a new kind of justice, one that would overcome the essential hypocrisy deeply rooted in the ontological system based on individual identities. Giorgio Agamben’s and Agata Bielik-Robson’s ideas are evoked in order to analyze the meaning of the chronicle “Mineirinho” (1962) and its relations with other canonic texts by the Brazilian author.